Estética, felicidade e satisfação com a vida na percepção dos idosos - Romanssini, Sabrina Fernanda (2020)
With the increase in population life expectancy, it is essential to study how the elderly can acquire longevity with happiness, more quality of life. Developing that being born brings a series of physiological and psychological changes, it is important to think about strategies to live well with health and good self-esteem at this stage. Feelings of freedom, security, aesthetics, satisfaction with life and happiness are relative and subjective to each human being. How people should have the right to choose those who look and feel safe. Therefore, the objective of this research is to identify the aesthetic perception, happiness and satisfaction with the lives of the elderly. It is a qualitative exploratory research with content analysis methodology, by Bardin (2016), with a semi-structured interview, focus group (FG) conducted from July to October 2019, with 25 elderly people, of both sexes, aged 60 years or over, in an aesthetic establishment. As interviews were conducted in a small municipality of 12 million inhabitants in the State of Rio Grande do Sul, each interview lasting 30 minutes. Participants are retired on a minimum wage. Result: in relation to aesthetics and beauty, most of the interviewees affirm that the interior beauty is superior and more important than the exterior beauty in people, however, a minority indicates that the exterior aesthetics must be fundamental for life. The happiness of living for the participants is being with the family, for helping others and being useful. In the question of following fashion and styles, as the answer was not directed to following fashion and your own style, but also to following fashion according to what suits you for your age and occurrence of departure. Final considerations: The incessant search for beauty and the aesthetic standards of the media manipulates a society. The insecurity of your image can lead to an imbalance between who the person is and who they want to be. Self-esteem is an acceptance or not of yourself. However, the interviewed participants have positive perceptions about their physical appearance, satisfaction with life, happiness, acceptance / adaptation with age, defense of a person's inner beauty as well as ethics, conduct, self-care, emotional balance, health, self- esteem and what quality of life, happiness is available for social contact, participation with the family, support, religious and cultural values.